PENGAPLIKASIAN MOTIF TRADISIONAL PADA DESAIN KEMASAN KECAP CAP GENTONG SEBAGAI STRATEGI PENGUATAN BRAND LOKAL - Eko Agung Sugiyarto; Maryami (Universitas Utpadaka Swastika, 2026)
The purpose of this study is to examine and integrate traditional Gentong motifs from Bantul Regency into the packaging design of Kecap Cap Gentong, a small and medium-sized enterprise (SME) product in the Special Region of Yogyakarta (DIY). By using a culture-based design approach, you can enhance local brand identity, increase product competitiveness, and expand market reach. Using a qualitative semiotic methodology, this study investigates the visual and symbolic meanings of applying Gentong motifs to packaging design, as well as how this impacts consumer perception and brand identity reinforcement. The study shows that the reconstruction of traditional motifs into modern packaging design is able to visually represent local cultural values and create aesthetic appeal that is in line with modern consumer preferences. The integration of traditional motifs not only serves as a decorative element, but also functions as a visual communication tool that strengthens the reputation of local brands and makes products unique in a competitive market.